PREMATURE HAIR GRAYING: INTEGRATING MECHANISMS, RISK FACTORS, AND THERAPEUTIC APPROACHES - Agata Wińska; Klaudia Zackiewicz; Michał Ziemba; Hanna Pietruszewska; Agata Ogórek; Paweł Liszka; Izabela Majchrzak; Hubert Bochenek (International Journal of Innovative Technologies in Social Science, 2025)
Premature graying of hair (PMGH) is a phenomenon resulting from the interaction of genetic, metabolic, and environmental factors, leading to melanocyte dysfunction in the hair follicle. This article discusses the key etiopathogenic mechanisms of PMGH, with particular emphasis on the roles of oxidative stress, micronutrient deficiencies, autoimmune processes, hormonal disorders, and metabolic alterations. Population data indicate that gender and ethnicity influence both the incidence and course of PMGH, while clinical observations suggest that it may serve as an early marker of endocrine, autoimmune, hematological, or cardiovascular disorders. Although the psychosocial burden varies, in many young individuals graying negatively affects their sense of attractiveness and overall mental well-being. Current therapeutic strategies include optimizing nutritional status, antioxidant supplementation, modulation of α-MSH pathways, as well as selected pharmacological treatments and phototherapy. Case reports confirm the possibility of partial or complete repigmentation. Despite a growing body of evidence, the pathogenesis of PMGH remains incompletely understood, highlighting the need for further research into the mechanisms underlying the reversibility of this process and the development of effective, targeted therapies.